Exercise Programming for Older Adults - Norman Kay A. Van (Human Kinetics, 1995)
This handbook sets the stage for safe and effective exercise programming by explaining the unique factors you need to consider when developing a program for seniors. Preface, Acknowledgements, Aging and Fitness, Aging World Populations, Exercise and Health in an Aging America, New Attitudes Toward Aging, Changing Fitness Needs, The Fitness Industry and an Aging Population, Exercise Science and Age-Related Changes in Functional Ability, Exercise Physiology and Aging Systems, Physical Conditions Requiring Special Consideration, Psychological and Social Aspects of Aging and the Benefits of Exercise, Meeting the Needs of Older Exercisers, General Program Components, Safety, Providing a Well-Rounded Exercise Program, Social and Emotional Components, Land-Based Programming, Chair Exercise, The Basic Exercise Class, Low-Impact Aerobics, Water-Based Programming, Special Considerations, General Class Format, Specific Water Exercises, Arthritis Water Exercise, Developing and Promoting your Senior Exercise Program, Needs Assessment, Identifying Appropriate Facilities, Promoting Your Exercise Program, Motivating Older Adults to Exercise, References, Index.